Autophagy, a Conserved Mechanism for Protein Degradation, Responds to Heat, and Other Abiotic Stresses in Capsicum annuum L. - Zhai, Yufei; Guo, Meng; Wang, Hu; Lu, Jinping; Liu, Jinhong; Zhang, Chong; Gong, Zhenhui; Lu, Minghui (Frontiers in Plant Science, 2016)
Abiotic stresses negatively affect plants growth and development by inducing protein denaturation, and autophagy degrades the damaged proteins to alleviate their toxicity, however, little is known about the involvement of autophagy in pepper (Capsicum annuum L.) tolerances to abiotic stresses. In this study, we identified autophagy-related gene (ATG) members in the whole genome of pepper by HMM method and analyzed their expression profiles in response to heat and other abiotic stresses by quantitative real-time PCR. The results showed that the CaATG contained 15 core ATG members including 29 ATG proteins with their respective conserved functional domains, involving the whole process of autophagy. Under normal environmental condition, the expression of CaATG genes showed tissue- and developmental stage-specific patterns, while under abiotic stresses of salt, drought, heat, cold and carbohydrate starvation, the accumulation of autophagosome punctate increased and the expression level of CaATG genes changed with stress type-dependent pattern, which indicates the linkage of autophagy in pepper response to abiotic stresses. After treated with heat stress, both the number of up-regulated CaATG genes and the increment of autophagosome punctate were higher in pepper thermotolerant line R9 than those in thermosensitive line B6, implying an association of autophagy with heat tolerance. In addition, CaATG6 was predicted to interact with CaHSP90 family members. Our study suggests that autophagy is connected to pepper tolerances to heat and other abiotic stresses.